(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The effect of different spawn seed on different variety show significant effect on mycelia running rate of oyster mushroom that reduced the required days to complete mycelium running in the spawn packet compared to the sawdust alone. Effect of different spawn seed on different variety found to be significant in yield contributing characters and yield of oyster mushroom with some extent. The highest biological yield, economic yield, dry yield, biological efficiency (BE) and benefit cost ratio (BCR) 264.9g, 259.3g, 25.17g, 86.90, 9.11% respectively was observed in maize based spawn seed on the Pleurotus florida variety. Effect of different spawn seed on different variety has a profound effect on chemical composition of oyster mushroom. Considering all the parameters in this experiment, maize based spawn seed on the Pleurotus florida variety is found promising for lowering the cost of production as well as increasing the yield and quality of fruiting body. Wheat based spawn seed on the Pleuorotus ostreatus variety may be the fair choice. Res. Agric., Livest. Fish.6(2): 181-192, August 2019